DNA-mediated Charge Transport in a Biological Context: Cooperation among Metalloproteins to Find Lesions in the Genome - Sontz, Pamela Alisa (California Institute of Technology, 2012)
Damaged bases in DNA are known to lead to errors in replication and transcription, compromising the integrity of the genome. A molecular wire, DNA conducts charge with shallow distance dependence, yet mismatches and lesions attenuate this process. We have proposed a model where repair proteins, containing redox-active [4Fe4S] clusters, utilize DNA charge transport (CT) to scan the genome for lesions. Based on this model, proteins are predicted to redistribute onto strands where DNA CT is inhibited. Using single-molecule atomic force microscopy (AFM) we have probed the redistribution of EndoIII, a base excision repair protein that contains a [4Fe4S] cluster. Consistent with the model, we find a redistribution of EndoIII onto DNA strands (3.8 kbp) containing C:A mismatch, which is not a specific substrate of EndoIII but inhibits CT. Proteins with mutations making them deficient in DNA-mediated CT do not similarly redistribute onto mismatched strands.

Various DNA-binding proteins, such as those involved in repair and pathways that maintain the integrity of DNA, have been found to contain FeS domains and other redox cofactors. We are discovering proteins from alternate repair pathways that may also utilize DNA CT to find damage. XPD, a 5′-3′ helicase involved in nucleotide excision repair, contains a conserved [4Fe4S] cluster and exhibits a DNA-bound redox potential that indicates it is able to carry out DNA CT. In AFM studies, we observe also the redistribution of XPD onto strands containing a mismatch. We further demonstrate that an XPD mutant, L325V, defective in carrying out DNA CT, does not redistribute onto mismatched strands.

DNA CT between distinct repair proteins bound to DNA was also probed by AFM. When XPD and EndoIII are mixed together, they coordinate in relocalizing onto mismatched strands. However, when a CT-deficient mutant of either repair protein is combined with the CT-proficient repair partner, no relocalization occurs. These data not only indicate a general link between the ability of a repair protein to carry out DNA CT and its ability to redistribute onto DNA strands near lesions but also provide evidence for coordinated DNA CT between repair proteins in their search for damage in the genome.
Keywords: Base Excision Repair; Atomic Force Microscopy; Chemistry; DNA-mediated Charge Transport; Iron-Sulfur Clusters; Repair Proteins